Belajar bahasa komputer BASIC mudah dan cepat Tigor Nauli Surawijaya, Roy Heru Trisnamurti - SURAWIJAYA, Tigor Nauli; Trisnamurti, Roy Heru (Gramedia Pustaka Utama, 1992)
ix, 108 hlm. : ilus. ; 21 cm.